Perceived Constraints in High-Density Apple Cultivation by the Farmers of the Mid-Hills Area of Himachal Pradesh - Singh, Shivani; Sharma, Priyanka; Saini, Manisha; Mehta, Piyush (International Journal of Economic Plants, 2023)
The study was carried out in area of Kandaghat and Solan blocks of Himachal Pradesh, India from November 2021 to April 2022 to study the constraints in high-density apple cultivation by the farmers of the mid-hills area of Himachal Pradesh, India. The present study fully relied on the primary data through a properly structured schedule for the production year 2021–2022, with a sample size of 60 farmers involved in high-density apple plantations. Garret’s ranking technique was used to find constraints perceived by the high-density apple cultivators. The objective of the research was to identify the prevailing problems of the high-density apple sector in the selected area. In this study the major problems faced by the high-density apple growers in production were the high cost of high-density apple plants, followed by identifying the disease, costly labor, and lack of technical guidance. Major marketing-related constraints expressed in the marketing of high-density apples were the problem of fluctuation of price, the high price of transportation, distant market, and high commission charges, further the data revealed that the major environmental and other related constraints were that the grading process and certification process seemed to be costly, problems from hailstorms were also found. The study also highlighted the need of proper marketing facilities as marketing helps in improving the living standard and eliminate the constraints in product and services.